Hydrolytic Stability of Sengon-Oriented Strand Board Bonded with Hybrid Phenol-Formaldehyde/Polymeric Methylene Diphenyl Diisocyanate Adhesives - Sari, Rita Kartika; Fitrianum, Fadilah; Maulana, Muhammad Iqbal; Hidayat, Wahyu; Winarni, Ina; Iswanto, Apri Heri; Lubis, Muhammad Adly Rahandi (Jurnal Sylva Lestari, 2024)
The hydrolytic stability of oriented strand board (OSB) is critical to guarantee good performance in humid conditions over the long term. The adhesive system impacts hydrolytic stability in addition to the wood strands. This study aims to investigate the hydrolytic stability of OSB bonded with a hybrid adhesive based on phenol-formaldehyde (PF) and polymeric methylene diphenyl diisocyanate (pMDI) modified with NaOH and CaCO3 catalyst. PF was mixed with each catalyst at approximately 1% of the PF solids content. The pMDI was added to the mixture at 2.5% and 5% of the PF solid content. The hybrid PF/pMDI adhesives were then used for OSB production. The hydrolytic stability of OSB samples was tested at 25°C and 100°C and compared with OSB using unmodified PF as a control. After hydrolysis, OSBs with hybrid PF/pMDI adhesives had lower weight loss than control adhesives at both temperatures. The pH indicates no significant polymer dissolution from the board into the hydrolysis solution. Hybrid PF/pMDI adhesives with a CaCO3 catalyst obtain significantly lower thickness swelling values. The findings of this study have significant implications for developing high-performance, environmentally-friendly OSB products. Keywords: eco-friendly composite, hydrolytic stability, oriented strand board, Paraserianthes falcataria, phenol-formaldehyde